Understanding science centre engagement in nurturing visitor interest and curiosity - Baniyamin, Nurhaya; Rashid, Md. Mizanur (2016)
Reaching and engaging visitors within exhibitions and throughout the museum environment, recurred as an area of design concern. Using the recent experience of Science Centre Singapore, The Mind Museum Philippines and The Experimentarium Denmark, the responses of the centre managements provided initial findings towards quality visitor experience and informal learning intentions. The biggest challenge is to provide an opportunity for cognitive and affective learning while collectively facilitating enjoyment and fun. Learning and educational theory are explored with implications for the exhibition development process. Nurturing visitor interest and curiosity theme reveal the centre's approach to offer a rich and cohesive experience.